Cyber-Hygiene Pada Informasi Sensitif Di Sektor Pemerintah - Juraida, Erni; Yazid, Setiadi (LPPM UNIVERSITAS BINA INSAN, 2024)
As reliance on digital systems increases, governments face significant challenges in protecting sensitive information from cyber threats. This research explores the effectiveness of cyber hygiene practices and regulations in maintaining the security of sensitive information in government entities. It highlights the importance of cyber hygiene practices, examines the role of regulation, evaluates its effectiveness, and identifies challenges in maintaining strong cyber security. The study was conducted using the Systematic Literature Review (SLR) method with the Kitchenham technique, reviewing 36 research publications selected from 612 papers published between 2018 and 2024. The results show that cyber hygiene practices in government have different characteristics compared to non-government organisations, given their potential impact on national security, diplomatic relations and public trust.